Product emotional classification in kansei engineering of perfume bottles - Tan, Ashley Wei Jin. (2011)
Consumers‟ needs and preferences have become complex and fast changing. Companies wanting to stay ahead of the competition can no longer depend on meeting the functional needs of the consumers. Many have begun to see the importance of developing a personal relation between the product and the user. Companies therefore have to also meet the psychological and emotional needs for the product.